Korelasi antara Pengetahuan dan Sikap terhadap Kontaminasi Arsenik pada Penjual Kerang Darah (Anadara granosa) di Pasar Tradisional di Surabaya Utara - Ardyanisa Raihan Kusuma; Nur Hasanah; Trias Mahmudiono (Universitas Airlangga, 2024)
Background: Indonesia, with its vast coastline, has become a major exporter of seafood products, including clams, generating millions of dollars in revenue. However, clams are frequently associated with foodborne illnesses, due to the presence of hazardous marine pollutants like arsenic. Objective: This research examines the connection between the knowledge and attitudes of sellers, regarding arsenic contamination in blood clams sold at traditional markets in North Surabaya. Method: The study employed a cross-sectional method, collecting primary data through direct interviews and questionnaires from 35 blood clam sellers in North Surabaya, as well as secondary data from previous studies. Results: The data were analyzed using the chi-square test, which indicated that there is / was no significant correlation between the sellers' knowledge and attitudes (p > 0.001). Conclusion: Consequently, it can be concluded that there is a lack of association between the sellers' knowledge and attitudes toward arsenic contamination in blood clams sold at traditional markets in North Surabaya, as evidenced by the high attitude scores (related to healthy practices) but low knowledge scores in the questionnaire.